Mechanism of maltose transport in Escherichia coli: transmembrane signaling by periplasmic binding proteins. - Davidson, A L (1992)
Maltose transport across the cytoplasmic membrane of Escherichia coli is dependent on the presence of a periplasmic maltose-binding protein (MBP), the product of the malE gene. The products of the malF, malG, and malK genes form a membrane-associated complex that catalyzes the hydrolysis of ATP to provide energy for the transport event. Previously, mutants were isolated that had gained the ability to grow on maltose in the absence of MBP. After reconstitution of the transport complex into proteoliposomes, measurement of the ATPase activity of wild-type and mutant complexes in the presence and absence of MBP revealed that the wild-type complex hydrolyzed ATP rapidly only when MBP and maltose were both present. In contrast, the mutant complexes have gained the ability to hydrolyze ATP in the absence of maltose and MBP. The basal rate of hydrolysis by the different mutant complexes was directly proportional to the growth rate of that strain on maltose, a result indicating that the constitutive ATP hydrolysis and presumably the resultant cyclic conformational changes of the complex produce maltose transport in the absence of MBP. These results also suggest that ATP hydrolysis is not directly coupled to ligand transport even in wild-type cells and that one important function of MBP is to transmit a transmembrane signal, through the membrane-spanning MalF and MalG proteins, to the MalK protein on the other side of the membrane, so that ATP hydrolysis can occur.